Fiduciary duty or loyalty? Evidence from co-opted boards and corporate misconduct - Zaman, Rashid; Atawnah, Nader; Baghdadi, Ghasan A.; Liu, Jia (Journal of Corporate Finance, 2021)
We examine the effect of co-opted boards on corporate misconduct and document a significant positive relationship. Utilising a large sample of public U.S. companies from the period 2001 to 2015, we find that a one standard deviation increase in the proportion of co-opted directors on a board leads to a 4.3% rise in corporate misconduct. This outcome is robust to a series of sensitivity tests and continues to hold after accounting for potential endogeneity concerns. Further analyses indicate that co-opted directors propose fewer board agenda items, exhibit lower attendance at board meetings, and receive compensation packages in excess of industry norms, which exacerbate stakeholder-agency conflicts. Cross-sectional analysis demonstrates that the documented relationship is most pronounced among firms with weak external monitoring, greater CEO-board social ties, boards whose members have high career concerns, and where CEO power is low. Additional tests reveal that co-opted directors engage in more environmental- and workplace-related violations than other types of stakeholder violations. Overall, our investigation generates original evidence that the presence of co-opted directors aggravates the incidence of corporate wrongdoing. Our study contributes to the continuing debate on the role of boards of directors and has policy implications for those responsible for devising and monitoring effective systems of corporate governance.